PENGARUH METODE MUROJA’AH TERHADAP KUALITAS HAFALAN AL-QUR’AN SANTRI TPA BANDAR LAMPUNG - SUSANTI, AGUS (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The muroja'ah method is to repeat memorization or memorize memorization that has been memorized/has been memorized to the tahfidz teacher. Muroja'ah is intended so that the memorization that has been memorized is maintained properly. Apart from a teacher, memorizing muroja'ah can be done alone or with friends. This research uses a quantitative experimental method with a Quasi Experimental design, in the form of a Nonequivalent Group Post-Test Only Design. The population in this study were TPA students at the Roudhlotul Munawwaroh Education Foundation in Bandar Lampung. The sample was taken using a simple random sampling technique and a total of 46 students were obtained. The data collection technique in this research used an oral test. The data analysis technique in this research is by using descriptive statistical analysis and t-test analysis (Independent Sample t-test) using the help of the IBM Statistical Package for Social Science (SPSS) version 25 program. The results of this research, based on descriptive statistical analysis, showed that the average quality of memorizing the Al-Qur'an in the experimental class was 88.57 and the average quality of memorizing the Al-Qur'an in the control class was 78.88. Based on the results of the average calculation, it shows that the quality of memorizing the Al-Qur'an for students who use the muroja'ah method is higher than students who use the Jibril method. Next, a t-test was carried out using the independent sample t-test using SPSS version 25, the results were Sig. (2-Tailed) is 0.00 with a confidence level of 95%. It can be interpreted that 0.00 < 0.05. So it can be concluded that H0 is rejected and H1 is accepted. This means